FRI0154 Incidence of Cancers in Patients with Rheumatoid Arthritis and a History of Cancer Treated with Rituximab or Abatacept. (9th June 2015) - Gottenberg, J.E.; Morel, J.; Ravaud, P.; Bardin, T.; Cacoub, P.; Cantagrel, A.; Combe, B.; Constantin, A.; Dougados, M.; Flipo, R.M.; Godeau, B.; Hachulla, E.; et al.
Abstract : Background: Patients with a history of cancer were excluded from pivotal clinical trials evaluating biologics. Therefore, only registries can inform us on the incidence of cancers in such patients treated with a biologic. Methods: Registries of the French Society of Rheumatology AIR and ORA included 1985 and 1024 patients to study tolerance and efficacy of rituximab and abatacept in common practice, respectively. Cancers and serious infections were validated by analysis of the charts of patients. Results: 258 patients had a history of cancer and 1552 patients did not have a history of cancer before rituximab (175 missing data). Among the 1552 patients without a history of cancer, 1549 patients had at last one follow-up visit (5344 patient-years) and 42 cancers occurred ( 0.8 cancers/100 patient-years ). Among the 258 patients with a history of cancer, 257 had at least 1 follow-up visit (867 patient-years) and 26 incident cancers ( 2.9 cancers/100 patient-years ), including 12 new cancers (1.3 cancers/100 patient-years) and 14 relapses of past cancers (1.6 cancers/100 patient-years). 54 patients had a history of cancer and 958 patients did not have a history of cancer before abatacept (12 missing data). Among the 958 patients without a history of cancer, 930 patients had at least 1 follow-up visit (2705 patient-years) and 36 cancers occurred ( 1.3 cancers/100 patient-years ). Among the 54 patients with a history of cancer, 53 patients had at least 1 follow-up visit (152 patient-years). Four incident cancers occurred ( 2.6 cancers/100 patient-years ) including 2 new cancers (1.3 cancers/100 patient-years) and 2 relapses of past cancers (1.3 cancers/100 patient-years). Conclusions: The incidence of cancers in the French national registries of patients with a history of cancer treated with rituximab or abatacept, approximately two-fold that of patients without a history of cancer, is comparable to that observed in the German RABBIT registry in patients with a history of cancer and rheumatoid arthritis treated with synthetic DMARDs or rituximab. Thus, until now, the risk of recurrence of cancer in patients with a history of cancer treated with rituximab or abatacept is in the range of what is expected in these patients at higher risk of cancer. Given the relatively short follow-up, it is necessary to continue to monitor patients with a history of cancer and to keep on evaluating the benefit/risk ratio before initiating a biologic, even a non anti-TNF biologic, in such patients. Disclosure of Interest: None declared